Instructional materials in teaching English verb tenses and aspects to Ilocano learners - Singson, Antonia B. 1926- ([s.n.], 1973)
Instructional materials for Ilocano learners of English verb tenses and aspects are presented in this study. It is discovered throughout the course of this study that English and Ilocano verbs express tense as well as aspect but Ilocano verbs have more aspect than tense. It was also found that Ilocano durative aspect can express present, past, future and perfected actions.